Effect of Increased CO2 And Temperature on Growth, Photosynthesis And Lipid Content of Tropical Algae - Teoh, Ming-Li; Wong, Chiew-Yen; Phang, Siew-Moi (Malaysian Journal of Science, 2013)
Increasing temperatures causally linked with anthropogenically elevated atmospheric carbon dioxide (CO2 ) levels characterise current ‘global warming’. Very little is known about how these factors will affect tropical microalgae. The aim of this study was to investigate the CO2 and temperature sensitivity of the photosynthetic process of two tropical Chlorella strains (Chlorella vulgaris UMACC 001 and Chlorella vulgaris UMACC 014). We grew cultures of the two strains under four conditions: (1) 28°C and 375 ppm CO2 (control), (2) 28°C and 750 ppm CO2 (high CO2 ), (3) 32°C and 375 ppm CO2 (high temperature), and (4) 32°C and 750 ppm CO2 (combined factors). Based on specifi c growth rate (μ), both Chlorella strains grew best under the combined factors of high CO2 level (750 ppm) and high temperature (32°C). Elevated CO2 stimulated the production of lipid in both strains. (Keywords: Chlorella, temperature, CO2 , photosynthesis )